Inhibition of several protein phosphatases by a non-covalently interacting microcystin and a novel cyanobacterial peptide, nostocyclin - Hastie, C. James; Borthwick, Emma B.; Morrison, Louise F.; Codd, Geoffrey A.; Cohen, Patricia T.W. (Biochimica et biophysica acta, 2005)
Microcystins produced by cyanobacterial ‘blooms’ in reservoirs and lakes pose significant public health problems because they are highly toxic due to potent inhibition of protein serine/threonine phosphatases in the PPP family. A dehydrobutyrine (Dhb)-containing microcystin variant [Asp 3, ADMAdda 5, Dhb 7]microcystin-HtyR isolated from Nostoc sp. was found to potently inhibit PP1, PP2A, PPP4 and PPP5 with IC 50 values similar to those of microcystin-LR. However, in contrast to microcystin-LR, which forms a covalent bond with a cysteine residue in these protein phosphatases, Asp,ADMAdda,Dhb-microcystin-HtyR did not form any covalent interaction with PP2A. Since the LD 50 for Asp,ADMAdda,Dhb-microcystin-HtyR was 100 μg kg −1 compared to 50 μg kg −1 for microcystin-LR, the data indicate that the non-covalent inhibition of protein phosphatases accounts for most of the harmful effects of microcystins in vivo. A 3-amino-6-hydroxy-2-piperidone containing cyclic peptide, nostocyclin, also isolated from Nostoc sp., was non-toxic and exhibited more than 500-fold less inhibitory potency towards PP1, PP2A, PPP4 and PPP5, consistent with the conclusion that potent inhibition of one or more these protein phosphatases underlies the toxicity of microcystins, both lacking and containing Dhb.